The Contribution of Leg Muscle Strength and Balance to Shooting Accuracy in UIR Soccer School (USS) Under 17 Athletes - Hidayat, Joni Taufik (Edumaspul: Jurnal Pendidikan, 2025)
This type of research is a multiple correlation. The population in this study is the Under 17 athletes from UIR Soccer School (USS), totaling 22 athletes. The sampling technique used in this research is the entire sample, with a total of 22 athletes. The test instruments used are the leg dynamometer test, passive balance test, and Shooting test. The data analysis technique used is the r-test. Based on the calculation results, it can be seen that (1) there is a contribution of leg muscle strength to the accuracy of Shooting in the Under 17 athletes from UIR Soccer School (USS) with an r-value of 0.521581 and a contribution of 27.20%, (2) there is a contribution of balance to the accuracy of Shooting in the Under 17 athletes from UIR Soccer School (USS) with an r-value of 0.517984 and a determinant contribution of 26.83%, (3) there is a contribution of strength and balance to the accuracy of Shooting in the Under 17 athletes from UIR Soccer School (USS) with an r-value of 0.735092 or a determinant contribution of 54.03%.